Development of a Calophyllum inophyllum-Loaded Biodegradable Chitosan-PVA Hydrogel: A Multifunctional Platform for HT-29 Colon Cancer Cell, and Antidiabetic Applications - Viswanathan, Akshaya; S, Sajith; M, Harini; Mathiyazhagan, Sivabalan; S, Vimal (Asian Pacific Journal of Cancer Biology, 2025)
Objective: Multifunctional hydrogels represent a promising strategy for localized and sustained drug delivery in cancer and chronic disease management. C. inophyllum, a medicinal plant with known bioactive properties, was explored in this study for its potential integration into a chitosan-polyvinyl alcohol (Cs-PVA) hydrogel system to enhance therapeutic efficacy. Methods: The Cs-PVA hydrogel was synthesized using a freeze-thaw technique and loaded with C. inophyllum extract. Structural and chemical characterizations were performed using Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM), confirming the incorporation and uniform dispersion of phytochemicals. In vitro cytotoxicity was assessed against HT-29 colon cells using the MTT assay. Antioxidant activity was evaluated using the DPPH assay, while anti-inflammatory potential was determined through protein denaturation inhibition. Drug release kinetics were analyzed over a 24-hour period, and α-amylase inhibition assays were performed to determine antidiabetic potential. Results: FTIR and SEM analyses confirmed successful integration of the extract within the hydrogel matrix. The hydrogel exhibited concentration-dependent cytotoxicity, with an IC₅₀ of 17 µg/mL, alongside visible apoptotic morphology in HT-29 cells. Antioxidant and anti-inflammatory activities showed 72.4% and 67.8% inhibition at 75 µg/mL, comparable to ascorbic acid and diclofenac, respectively. The hydrogel achieved nearly 100% drug release within 24 hours. Antidiabetic activity was demonstrated by 67.1% α-amylase inhibition at 50 µg/mL, close to metformin’s 79.3%. Conclusion: The C. inophyllum-loaded Cs-PVA hydrogel shows strong potential as a biodegradable, multifunctional therapeutic platform, offering cytotoxic, antioxidant, anti-inflammatory, and antidiabetic effects for future cancer and chronic disease treatments.